Dinuclear Face‐Sharing Bi‐octahedral Tungsten(VI) Core and Unusual Thermal Behavior in Complex Th Tungstates. Issue 21 (27th March 2015) - Xiao, Bin; Gesing, Thorsten M.; Robben, Lars; Bosbach, Dirk; Alekseev, Evgeny V.
Abstract Two new thorium tungstates A6Th6(WO4)14O (A=K and Rb) were synthesized by high‐temperature solid‐state reactions. The structures of both phases are based on a rare dinuclear confacial bi‐octahedral [W2O9]6− core, encapsulated in a [Th6W7O46(W2O9)]32− cage showing a cross‐section geometry similar to a six‐leafed lily. The adjacent cages are connected in two dimensional layers by WO4 tetrahedral linkers. Due to the dissimilarities in mutual orientations of adjacent layers in these two structures, K6Th6(WO4)14O crystallizes in space group of R32 while Rb6Th6(WO4)14O stabilizes in P<alternatives> <![CDATA[6]]> <inline-graphic xlink:href="ark:/27927/pgjkz2nb3t" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>2c. The high‐temperature phase transition was observed in Rb6Th6(WO4)14O and investigated using high‐temperature PXRD technique. The results demonstrate a very unusual thermal behavior of this compound. The Raman and IR spectra of both phases were analyzed with respect to their complex structures.